Analisis Tantangan dan Pemanfaatan Sistem Informasi Manajemen (SIM) dalam Mendukung Pengambilan Keputusan Strategis: Studi Kualitatif di Dinas Dikpora Kabupaten Dompu - Nur Alya; M. Ikhwan Mansyuri; Shoalihin Shoalihin (Journal of Management and Creative Business, 2026)
This study aims to explore the impact of management information system (MIS) quality on strategic decision-making within organizations. The focus of the analysis lies in examining how the quality of the management information system affects the effectiveness and efficiency of strategic decision-making, while identifying critical elements that influence this relationship. The research employs a mixed-method approach qualitative analyses, including SWOT analysis for data collection and processing. The findings indicate that a high-quality management information system significantly influences the effectiveness and efficiency of strategic decision-making. The novelty of this research lies in its analytical approach, which integrates the perspective of internal organizational challenges with the strategic utilization of MIS within the context of local government institutions. Unlike previous studies that primarily focus on technical effectiveness or technological aspects, this research highlights how the integration of MIS can enhance the quality of strategic decision-making within educational bureaucracies, particularly in the Office of Education, Youth, and Sports (Dikpora) of Dompu Regency.